Peripheral circadian clock for the cuticle deposition rhythm in Drosophila melanogaster - Ito, Chihiro (National Academy of Sciences, 2008)
Insect endocuticle thickens after adult emergence by daily alternating deposition of two chitin layers with different orientation. Although the cuticle deposition rhythm is known to be controlled by a circadian clock in many insects, the site of the driving clock, the photoreceptor for entrainment, and the oscillatory mechanism remain elusive. Here, we show that the cuticle deposition rhythm is regulated by a peripheral oscillator in the epidermis in Drosophila melanogaster. Free-running and entrainment experiments in vitro reveal that the oscillator for the cuticle deposition rhythm is independent of the central clock in the brain driving the locomotor rhythms. The cuticle deposition rhythm is absent in null and dominant-negative mutants of clock genes (i.e., period, timeless, cycle, and Clock), indicating that this oscillator is composed of the same clock genes as the central clock. Entrainment experiments with monochromatic light–dark cycles and cry(b) flies reveal that a blue light-absorbing photoreceptor, cryptochrome (CRY), acts as a photoreceptor pigment for the entrainment of the cuticle deposition rhythm. Unlike other peripheral rhythms in D. melanogaster, the cuticle deposition rhythm persisted in cry(b) and cry(OUT) mutant flies, indicating that CRY does not play a core role in the rhythm generation in the epidermal oscillator.